Innovative Approaches to Teach English Speaking for Tourism: The Impact of AI and Social Media - Putri, Andi Mega Januarti; Nurul Imansari; Asdar (Universitas Sulawesi Barat, 2024)
As a region with rich cultural heritage and maritime beauty, Majene required efforts and community involvement to maximize its tourism potential. This included the enhancement and training of English language skills among the community and its human resources for the dissemination of information and to attract international tourists. This study aimed to assess the impact of using technologies such as AI (Fully Fluent) and social media (Instagram) in developing English-speaking skills for tourism at Universitas Sulawesi Barat. This research was a descriptive quantitative study, in which a Likert scale questionnaire based on the Technology Acceptance Model (TAM) was administered to 25 English Education students at Universitas Sulawesi Barat. The findings revealed that the average mean score obtained from the questionnaire was 3.408, which falls under the 'very high' category. Among the TAM components, 'Perceived Ease of Use' had the highest mean score, followed by 'Perceived Usefulness,' 'Behavioral Intention to Use,' and 'Attitude toward Use,' all of which were categorized as 'very high,' while 'Actual System Use' ranked last in the 'high' category. These results indicated that the use of AI and social media was perceived as having a very positive impact on the students of Universitas Sulawesi Barat, particularly in terms of the ease and effectiveness which implied that it is applicable for English speaking practice for specific purpose included tourism. Contribution : this study can serve as a relevant reference and guide in the field of English education, particularly in the area of English for specific purposes, with a focus on speaking skills.